Distal Radioulnar Joint, Distal Ulna Injury, and Lunate Facet Considerations in Distal Radius Fractures. (September 2021) - Rubio, Francisco
Abstract : Summary: Injuries to the distal aspect of the ulna and the distal radioulnar joint (DRUJ) commonly occur concurrently with distal radius fractures. These fractures may also involve the sigmoid notch of the lunate facet of the radius. Each of these structures merits consideration when managing ulnar-sided injuries associated with distal radius fractures. Improper management of distal radioulnar complex injuries may result in limited wrist motion, persistent DRUJ instability, and pain despite successful fracture union. The distal ulna is the keystone of the distal radioulnar articulation. An understanding of the components of the distal radioulnar complex and methods to manage injuries of each of these components contributes to improved functional outcomes by restoring this keystone effect. The classification of distal radioulnar injuries discussed herein provides a framework for understanding the disruption of the ligamentous stabilizers of the DRUJ and identifying residual distal radioulnar instability after fracture fixation. Proper treatment of residual DRUJ instability will restore stability and minimize persistent functional impairment.